Nanomaterials as stationary phases and supports in liquid chromatography. Issue 19 (23rd August 2017) - Beeram, Sandya R.; Rodriguez, Elliott; Doddavenkatanna, Suresh; Li, Zhao; Pekarek, Allegra; Peev, Darin; Goerl, Kathryn; Trovato, Gianfranco; Hofmann, Tino; Hage, David S.
Abstract: The development of various nanomaterials over the last few decades has led to many applications for these materials in liquid chromatography (LC). This review will look at the types of nanomaterials that have been incorporated into LC systems and the applications that have been explored for such systems. A number of carbon‐based nanomaterials and inorganic nanomaterials have been considered for use in LC, ranging from carbon nanotubes, fullerenes and nanodiamonds to metal nanoparticles and nanostructures based on silica, alumina, zirconia and titanium dioxide. Many ways have been described for incorporating these nanomaterials into LC systems. These methods have included covalent immobilization, adsorption, entrapment, and the synthesis or direct development of nanomaterials as part of a chromatographic support. Nanomaterials have been used in many types of LC. These applications have included the reversed‐phase, normal‐phase, ion‐exchange, and affinity modes of LC, as well as related methods such as chiral separations, ion‐pair chromatography and hydrophilic interaction liquid chromatography. Both small and large analytes (e.g., dyes, drugs, amino acids, peptides and proteins) have been used to evaluate possible applications for these nanomaterial‐based methods. The use of nanomaterials in columns, capillaries and planar chromatography has been considered as part of these efforts. Potential advantages of nanomaterials in these applications have included their good chemical and physical stabilities, the variety of interactions many nanomaterials can have with analytes, and their unique retention properties in some separation formats.